Decentralization as a disincentive for transnational terror? An empirical test - Axel Dreher; Justina A. V. Fischer (Stockholm School of Economics, The Economic Research Institute (EFI), 2007)
Using panel data for a maximum of 109 countries over the years 1976-2000, we empirically analyze the impact of decentralization on the occurrence of transnational terror. Taking account of the potential simultaneity between terror and decentralization, our results show that expenditure decentralization robustly reduces the number of terror events in a country, while political decentralization has no impact.
Keywords: D74; H40; H70; 330; Terrorism; Decentralization; Democracy; Politische Gewalt; Dezentralisierung; Verwaltungsstandort; Politische Entscheidung; Panel; Welt